President's Message - McKay, Marcy (Operating Room Nurses Association of Canada Journal, 2005)
I hope you all enjoyed a safe and happy summer. Time certainly does fly by! As this issue is delivered to your door, read through and see what the conference in Montreal was all about. The conference planning committee did a wonderful job of showing off their city to all 1000+ delegates. From the Opening Ceremony, complete with acrobatics, to the closing speaker, who got all of us dancing, it was a constant whirlwind of culture, education and excitement!